Evidence of in vivo exogen protein uptake by red blood cells: a putative therapeutic concept - Hertz, Laura (2023)
For some molecular players in red blood cells (RBCs), the functional indications and molecular evidence are discrepant. One such protein is transient receptor potential channel of canonical subfamily, member 6 (TRPC6). Transcriptome analysis of reticulocytes revealed the presence of TRPC6 in mouse RBCs and its absence in human RBCs. We transfused TRPC6 knockout RBCs into wild-type mice and performed functional tests. We observed the "rescue" of TRPC6 within 10 days; however, the "rescue" was slower in splenectomized mice. The latter finding led us to mimic the mechanical challenge with the cantilever of an atomic force microscope and simultaneously carry out imaging by confocal (3D) microscopy. We observed the strong interaction of RBCs with the opposed surface at around 200 pN and the formation of tethers. The results of both the transfusion experiments and the atomic force spectroscopy suggest mechanically stimulated protein transfer to RBCs as a protein source in the absence of the translational machinery. This protein transfer mechanism has the potential to be utilized in therapeutic contexts, especially for hereditary diseases involving RBCs, such as hereditary xerocytosis or Gárdos channelopathy.